World on the line. - Staple, Gregory (Geographical Magazine (London, England: 1995), 1993)
Despite the huge social impact of the global telephone network, we remain surprisingly ignorant of our telegeography. The global telephone network is now composed of over 600 million telephone exchange lines linking over a billion phone and computer terminals in over 180 countries: it is by far the largest machine we have ever built. Since 1989, the London-based International Institute of Communications has been surveying the volume and destination of telephone traffic from over 50 countries. In 1992, international telephone and fax traffic came to a total of over 40 billion minutes. Around 55 percent of this traffic centered around the U.S., Germany, and Japan. Despite the current boom in traffic, regions such as Sub-Saharan Africa (excluding South Africa) and the Indian subcontinent remain teledeserts. Sidebars discuss the advent of telecommunications service providers and patterns associated with social telephone usage.